Ibrahim, Abu Bakr Ahmad. “The Concept of Integration of Knowledge and its Relation to the Islamization of Knowledge Movement,” Year 11, Issues 42-43 (Fall 1426 AH/ 2005 CE), Pp. 11-52. - إبراهيم أبو بكر محمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2006)
Abu Bakr Ibrahim’s article discusses the concept of integration of knowledge and its relation to the concept of Islamization of knowledge, the main challenges that face this concept, and illustrations of epistemological responses to these challenges. It also addresses the efforts that made knowledge integration an important element in attempts at comprehending and overcoming a number of intellectual theses that treat the issue of revival/renaissance, and discusses the concepts and perceptions of the Western experience. The article is based on an analytical and critical study of related literature, including conducting interviews with a number of academics working on the subject of the integration of knowledge and, in particular, those active in work on the Islamization of knowledge.